2012
DOI: 10.1557/jmr.2012.384
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical properties of visible active photocatalytic WO3 thin films prepared by reactive dc magnetron sputtering

Abstract: Nanostructured tungsten trioxide films were prepared by reactive dc magnetron sputtering at different working pressures P tot 5 1-4 Pa. The films were characterized by scanning electron microscopy, x-ray diffraction, Rutherford backscattering spectroscopy, Raman spectroscopy, and ultraviolet-visible spectrophotometry. The films were found to exhibit predominantly monoclinic structures and have similar band gap, E g % 2.8 eV, with a pronounced Urbach tail extending down to 2.5 eV. At low P tot , strained film s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 65 publications
(81 reference statements)
0
48
1
Order By: Relevance
“…25 These trap states were associated with oxygen vacancies in the thin film, and the measured concentrations correlated well with previous approximate values obtained from near infrared (NIR) absorption. 24 An oxygen vacancy concentration of x ≈ 0.005 (determined by an average over three films) was inferred in the more sub-stoichiometric WO 3-x films, prepared at P tot = 10 mTorr, while the less sub-stoichiometric films prepared at P tot = 30 mTorr showed vacancy concentrations of x ≈ 0.001 (determined by an average over four films). 25 It was shown that the films mainly exhibited the monoclinic γ-WO 3 phase with a fraction of the monoclinic ε-phase and a slight strain in films primarily at P tot = 10 mTorr.…”
Section: A Thin Film Fabricationmentioning
confidence: 95%
See 3 more Smart Citations
“…25 These trap states were associated with oxygen vacancies in the thin film, and the measured concentrations correlated well with previous approximate values obtained from near infrared (NIR) absorption. 24 An oxygen vacancy concentration of x ≈ 0.005 (determined by an average over three films) was inferred in the more sub-stoichiometric WO 3-x films, prepared at P tot = 10 mTorr, while the less sub-stoichiometric films prepared at P tot = 30 mTorr showed vacancy concentrations of x ≈ 0.001 (determined by an average over four films). 25 It was shown that the films mainly exhibited the monoclinic γ-WO 3 phase with a fraction of the monoclinic ε-phase and a slight strain in films primarily at P tot = 10 mTorr.…”
Section: A Thin Film Fabricationmentioning
confidence: 95%
“…More information about the experimental details can be found elsewhere. 23,24 The O 2 /Ar ratio was kept at 0.43, and the samples were sputtered at a substrate temperature of T s = 553 K, and post-annealed at T a = 673 K for 1 h in air. Samples were sputtered at working pressures, P tot = 10, 15, 20, 25 and 30 mTorr.…”
Section: A Thin Film Fabricationmentioning
confidence: 99%
See 2 more Smart Citations
“…Films deposited at 600 • C are in full deep -blue color and the transmittance of the film reduced to 20% and can be attributed to the release of oxygen during the deposition process. 14,15 With a further increment in substrate temperature up to 800 • C, the transmittance of the film increases to 70%; this shows the evidence of thermochromic nature in BWO films. In addition, there are two regions, where a transparent oscillating region and a region of strong absorption.…”
Section: Resultsmentioning
confidence: 74%